Pathogenesis of Colitis in Germ-Free Mice Infected With EHEC O157:H7. (July 2017) - Eaton, K. A.; Fontaine, C.; Friedman, D. I.; Conti, N.; Alteri, C. J.
Enterohemorrhagic Escherichia coli (EHEC) are strains of E. coli that express Shiga toxins (Stx) and cause hemorrhagic colitis. In some cases, disease can progress to hemolytic uremic syndrome, a potentially fatal form of kidney disease. Both enteric and renal disease are associated with the expression of stx genes, which are often carried on lysogenic phage. Toxin is expressed following induction and conversion of the phage to lytic growth. The authors previously used a germ-free mouse model to demonstrate that toxin gene expression is enhanced during growth in vivo and that renal disease is dependent on both prophage induction and expression of Stx2. In the current study, the authors document and quantify necrotizing colitis, examine the progression of enteric and renal disease, and determine the role of Stx2, phage genes, and the type 3 secretion system (T3SS) in bacterial colonization and colitis and systemic disease. By 1 day after inoculation, EHEC-monocolonized mice developed colitis, which decreased in severity thereafter. Systemic disease developed subsequently. Infection with EHEC mutant strains revealed that renal failure and splenic necrosis were absolutely dependent on the expression of Stx2 but that T3SS function and prophage excision were not necessary for systemic disease. In contrast, colitis was only partly dependent on Stx2. This study demonstrates that in germ-free mice, like in human patients, EHEC causes early colitis followed by renal failure and that systemic disease but not colitis is Stx2 dependent.